Investigating triclopyr vapor and particle drift in roadside settings - Estefania G. Polli; Travis W. Gannon; Ronald R. Rogers; Mathieu C. LeCompte; Khalied Ahmed (Agrosystems, Geosciences & Environment)
Abstract Triclopyr is a synthetic auxin herbicide widely used to manage roadside vegetation due to its effective, selective, and prolonged action on broadleaf species, as well as its low toxicity to humans and animals. However, if triclopyr drifts from the roadside into agricultural lands, it can result in injury and yield loss of sensitive crops. The objective of this study was to characterize and quantify particle and vapor drift of triclopyr as influenced by formulation, season, and nozzle type under roadside conditions. Field studies were conducted on a roadside located along Interstate 540 in Morrisville, NC, in 2022 and 2023. Triclopyr amine and choline were applied at 3363 g a.e. ha−1 using Boominator and Nutating nozzles. Active air samplers were used to collect vapor drift within 48 h after application, while deposit cards were used to collect particle drift 10 min after application. Triclopyr vapor concentration peaked within the first 24 h after application, with the concentration of triclopyr amine being 29% higher than triclopyr choline during this period. Additionally, vapor concentrations of triclopyr were higher during spring and summer compared to fall and winter. No differences in triclopyr particle deposit and drift distance were observed between formulation and nozzle type. Triclopyr was detected at very low levels (< 2% of field rate) within 3 m from the treated area. This study provides valuable insight into triclopyr volatilization, emphasizing temporal, formulation, and seasonal variations, while also addressing the consistency in particle drift between triclopyr formulations and nozzle types.